Numerical and experimental investigations of novel nature inspired open lattice cellular structures for enhanced stiffness and specific energy absorption. (June 2022) - Dara, Ashok; Bahubalendruni, MV A.Raju; Johnney Mertens, A.; Balamurali, Gunji
Abstract: Lattice structures are meant for light weight structure with a high strength to weight ratio used to carry high loads and high energy absorption capabilities. In the lattice structures, the non-stochastic arrangement of members has the ability to control and customize their mechanical properties. The recent developments in additive manufacturing provides freedom in design and gives flexibility to manufacture tailored complex novel lattice structures. In the present investigation, the traditional 2.5D honeycomb and the tessellated open lattice structures with basic crystalline arrangements of the members are considered to study the load carrying capacity, stiffness and energy absorption capabilities by keeping constant volume for each lattice. The results through the experiments and finite element analysis are compared with a novel open lattices structure to show significant improvement in stiffness and high energy absorption with the volume of the material. However, the novel open lattice structure has displayed prominent post yield plateau stresses and energy absorption with sacrificing stiffness and strength significantly. Graphical Abstract: ga1